Práticas discursivas sobre a violência contra as mulheres na contemporaneidade: uma crítica feminista à objetividade dos números e a centralidade da judicialização - MARCIA PAULINO DA SILVA LOPES (2024)
Domestic and family violence against women is a historical and sociocultural phenomenon that manifests itself from gender inequalities and asymmetric power relations, which produce relations of domination by men and subordination of women in different parts of the world and in different times. This research has as a goal to understand and to analyze the discursive practices about the domestic and family violence against women, having the social psychology as a theoretical basis, from a socio-constructionist perspective, in dialogue the gender studies on feminist epistemologies. The methodological paths start from the National Policy Plans for Women as Documents of Public Domain in research characterized as qualitative, analytical, descriptive and explanatory. We questioned the construction of discursive practices of public policies to combat violence against women from two aspects, the construction of numbers as an absolute truth, and the perspective of punitive judicialization as central, nowadays. Guided by the intersectional approach, we position our criticism, proposing the expansion of the role of social psychology as essential to the combat to the violence against women. Aiming to contribute to the work of psychology professionals with women victims of violence, we list some methodologies understood as potential resources for transformation within the scope of women's subjectivity and the socio-cultural context that perpetuates gender-based violence against women.